S’identifier à l’aube de l’état civil (nufûs). Les justiciables devant le tribunal civil de Homs (Syrie centrale) à la fin du xixe siècle - Vanessa Guéno (Revue des Mondes Musulmans et de la Méditerranée)
This article is based on the records of hearings between 1886 and 1919 before the civil court and the criminal justice court of first instance (niẓâmî) of Homs. It presents the different modes of identification for individuals and groups. Administrators, subjects, court personnel, witnesses, informants and others must identify themselves or be identified. After the creation of the Registry Office (Law of October 14, 1890), introducing oneself before the court became a set of well-defined procedures. However, some differences in form and choice of personal identification components allow us to consider how Ottoman legal system was locally applied.